GATA3 expression in pulmonary mucinous adenocarcinoma presenting as a distant metastasis: A case report - Nada Shaker; CeCelia Hanline; Isabella M. Tynski; Zofia Tynski; Chiemezie C. Amadi; Anil Parwani; Konstantin Shilo (Elsevier, 2022)
A 75-year-old female with 50 pack-year history of smoking was found to have a right upper lobe adenocarcinoma with metastatic soft tissue chest wall deposit. The tumor's immunohistochemical profile at both sites was significant for expression of CK7 and GATA3, but not TTF1 and Napsin A. Furthermore, by next generation sequencing the tumor harbored concurrent KRAS G12A and BRAF D594H mutations and had no alterations in ERBB2 gene. Our case is unique as this unusual immunoprofile with GATA3 expression that is preferentially expressed in breast and urothelial carcinomas was observed in mucinous adenocarcinoma of the lung presenting as a distant metastasis.